Efficacy and safety of the third-generation tyrosine kinase inhibitor Olverembatinib in relapsed and persistent minimal residual disease positive Philadelphia chromosome-positive acute lymphoblastic leukemia patients - Jiang, Xinwen; Zhou, Minran; Ma, Junjie; Ji, Qingli; Li, Xiaoqing; Ma, Sai; Chen, Chunyan (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to evaluate the efficacy of Olverembatinib in patients with relapsed and persistent minimal residual disease-positive Philadelphia chromosome-positive acute lymphoblastic leukemia.MethodsWe conducted a retrospective analysis of clinical characteristics in 22 patients diagnosed with Ph + ALL at Qilu Hospital of Shandong University and Yantai Yuhuangding Hospital between December 2018 and December 2024.ResultsA cohort of 22 patients with Ph + ALL was enrolled in this study. Among them, 12 (54.5%) patients had relapsed Ph + ALL, while the remaining 10 patients exhibited persistent MRD positivity. In the relapsed subgroup, the CR rate following one treatment cycle reached 75.0% (9/12), with MRD-negative and MMR rates of 75.0% (9/12) and 50.0% (6/12), respectively. Upon completion of two treatment cycles in evaluable patients (n = 8), the CR, MRD-negative, and MMR rates all rose to 87.5, 87.5 and 87.5%, respectively. The patients with forfeited MMR on first or second-generation TKIs, of which the MMR rate was restored to 60.0% (6/10) after one cycle of Olverembatinib treatment, and a pleasant surprise was that their MMR rate soared to 90% (9/10) after two cycles of Olverembatinib treatment. 70% of them subsequently underwent successful hematopoietic stem cell transplantation.ConclusionThe efficacy and tolerability of Olverembatinib were confirmed in patients with relapsed, MRD-positive, Ph + ALL, offering a novel therapeutic approach for these patients and making prolonged survival possible.